Impact of SGLT2-inhibitors on acute kidney injury in diabetic patients with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI) - Pasquale Paolisso; Marta Belmonte; Emanuele Gallinoro; Roberto Scarsini; Luca Bergamaschi; Leonardo Portolan; Matteo Armillotta; Giuseppe Esposito; Elisabetta Moscarella; Claudio Montalto; Elayne Kelen de Oliveira; Francesco Angeli; et al. (Cardiovascular Diabetology)
Abstract Background Acute kidney injury (AKI) following transcatheter aortic valve implantation (TAVI) is associated with significantly worse outcomes, leading to increased short- and long-term mortality. We sought to evaluate the impact of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on the risk of AKI in patients with type 2 diabetes mellitus (T2DM) and severe aortic stenosis (AS) undergoing TAVI. Methods Multicenter international registry of consecutive T2DM patients with severe AS undergoing TAVI between 2021 and 2024. The study population was stratified by the presence of chronic kidney disease (CKD), defined according to the KDIGO guideline, and anti-diabetic therapy at hospital admission (SGLT2i versus no-SGLT2i users). AKI was defined according to the Valve Academy Research Consortium 3 (VARC-3) criteria. Results The study population consisted of 514 patients stratified into those without CKD (n = 226, 44%), of whom 43 (19%) were treated with SGLT2i, and 288 (56%) with CKD, of whom 71 (24.7%) were on SGLT2i treatment. The median age was 81 [77–84] years, and 60.1% were males. SGLT2i use did not impact renal function in patients without CKD, with AKI occurring in 7.1% of the cases, regardless of SGLT2i use. Among CKD patients, AKI occurred more frequently in no-SGLT2i users compared to those receiving SGLT2i (19.8% versus 8.5%, p = 0.027), with a significant increase in post-TAVI and discharge serum creatinine values for no-SGLT2i users (p = 0.001 after TAVI and p < 0.001 at hospital discharge). Only in the CKD group, the use of SGLT2i was identified as an independent predictor of a lower rate of AKI (OR 0.70, 95%CI 0.42–0.91, p = 0.014). Patients who developed AKI had a higher incidence of major adverse cardiovascular events during follow-up, regardless of CKD (p < 0.025 for both groups). Conclusion In diabetic patients with CKD undergoing TAVI, SGLT2i therapy was associated with a lower occurrence of AKI compared to those not treated with SGLT2i, suggesting a potential nephroprotective effect in this high-risk population. Graphical abstract Summary of the main findings of the study.